Effect of Video Game Usage on Academic Performance of Medical Students in King Abdulaziz University - Ahmed A. Aljohaney, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Habitual playing of video games is believed to have a harmful effect on the academic performance of students. This study tracks the effect of video game playing on the academic performance of medical students in Saudi Arabia. During May through August 2013, 307 medical students in their final years filled a cross-sectional survey to collect data on the use of video games at King Abdulaziz University. Results showed female students played video games less than male students. Additionally, video game users were more likely than nonusers to have scores between 4.0 and 4.4 on a 5 point grade point average scale. While higher scoring students were less likely to play video games, only 25.6% of the surveyed students could be included in that category, and 71.8% of those students played video games for < 1 hr /day. Students who played video games for > 1 hr/day had a lesser chance (50.4%) of scoring within the highest range of grade point averages. The results indicate that while limited use of video games may improve grade point average scores, video gaming could not be recommended for students who want to score in the highest tier of grade point averages. A large-scale multi-institutional study is required to confirm these observations.